How organizational trust impacts organizational citizenship behavior: Organizational identification and employee loyalty as mediators - Dai, Yuping; Tang, Yuk Ming; Chen, Weinian; Hou, Jie (Frontiers in Psychology, 2022)
Research on the influence of organizational trust (OT) on organizational citizenship behavior (OCB) of employees has been conducted for years, but the influence of internal mechanism for OT on OCB are not well studied. Based on social exchange theory and organizational identity theory, this paper explored the OT on the OCB and revealed the chain mediating role of organizational identification (OI) and employee loyalty (EL) from both employees cognitive and psychological perspectives. The research employed a two-wave and multi-source strategy to conduct hypothesis validation with 305 validated questionnaires of Chinese enterprises. The results of the empirical analysis show that: (1) OT has a significant effect on OCB; (2) OI plays a mediating role between OT and OCB; (3) EL plays a mediating role between OT and OCB; (4) OI and EL have a significant chain-mediating role between OT and OCB. The results of this study have deepened the understanding of organizational trust and have important practical implications for improving organizational citizenship behavior, organizational identity and employee loyalty.